A Multi-Purpose Mini Hybrid Fuel Cell-Battery-Solar Portable Device For Rural Applications: Laboratory Testing - M., O. Abdullah; Y., K. Gan; K., M.Tay; N., Julai (International journal of recent research and applied studies, 2011)
In this study, a novel multipurpose portable PEM fuel cell-solar-battery system was custom designed, constructed and laboratory tested, specially aims for applications in the rural areas remote from conventional electric power grid. We obtain encouraging results which show the applicability of such system for used as a multipurpose kit for portable applications. Our study shows that various power sources namely solar cell, battery and PEM fuel cells can combine harmoniously to obtain higher power voltage, whilst maintaining their individual advantages – such as good startup performance. Our typical results show that the maximum power of the PEM fuel cell/solar/battery with load is in the range of 2.4W-2.7W which can be maintained continuously. Apart from good cold start characteristic, the portable system also exhibits stable voltage, compact in size and acceptable in weight, hence suitable for rural power application at places remote from conventional grid.